Discovery of Jaschnovia brevis (Farran, 1936) in the Barents Sea and its peculiarities of spatial distribution. Obnaruzheniye vida Jaschnovia brevis (Farran, 1936) v Barentsevom more i osobennosti yego prostranstvennogo raspredeleniya. - Berchenko, I.V. & O.L. Zimina (Principy Ekologii, Principles of the Ecology, 2019)
The work is devoted to study of ecological peculiarities of the species colanoid copepod Jaschnovia brevis. It was found in the border area of the ice extend in the North-Western part of the Barents Sea during two expeditions of R/V "Dalniye Zelentsy" in July and November 2017. The species has been recorded in the Barents Sea for the first time. Significant differences in the spatial distribution of J. brevis and ice amphipods found in the studied water area were noted. On the basis of the obtained data and available literature the validity of the classification of the species belonging to autochthonous ice fauna was discussed. The relationship of J. brevis ecology features to abiotic factors such as depth, temperature range, and salinity, as well as their role in species distribution, was considered.